Emerging Data on the Safety and Efficacy of Transurethral Water Vapour Therapy for Benign Prostatic Hyperplasia - Jones, Patrick (Res Rep Urol, 2021)
Benign prostate disease is a disease of prevalence and over 25% of men affected by bothersome lower urinary tract symptoms (LUTS) as a result of it will require surgical intervention during their lifetime. While transurethral resection of the prostate (TURP) has served as the cornerstone treatment for many years, there now exist a multitude of minimally invasive alternatives including the Rezum system. The latter is a novel form of transurethral water vapour therapy, which is attracting increasing attention. It utilizes convective water vapour energy (WAVE) and thereby radiofrequency (RF) in order to generate heat energy. Early studies have demonstrated promising results. To date there have been 12 studies published on Rezum, however only one randomized trial. This review offers an overview and evaluation of this emerging evidence.